Borrelial phosphomannose isomerase as a cell surface localized protein that retains enzymatic activity and promotes host-pathogen interaction - Shraboni Dutta; Vipin S. Rana; Brian T. Backstedt; Anil K. Shakya; Chrysoula Kitsou; Ozlem B. Yas; Alexis A. Smith; Michael H. Ronzetti; Rachel M. Lipman; Sarai Araujo-Aris; Xiuli Yang; Ganesha Rai; et al. (mBio)
ABSTRACT All organisms produce an intracellular Zn2+-dependent enzyme, phosphomannose isomerase (PMI) or mannose-6 phosphate isomerase, that catalyzes the reversible conversion of mannose-6-phosphate and fructose-6-phosphate during sugar metabolism and polysaccharide biosynthesis. Unexpectedly, we discovered an additional PMI function in Borrelia burgdorferi, the pathogen of Lyme disease, where the enzyme is localized on the cell surface and binds to collagen IV—a host extracellular matrix component predominantly found in the skin. The AlphaFold 3-based structural model of B. burgdorferi PMI (BbPMI) retains the active site with tetrahedrally-coordinated Zn2+ seen in other PMIs of known structure, residing in an elongated crevice. Ligand docking shows that the crevice can accommodate the tip trisaccharide moiety of a glycosylated asparagine residue on the collagen IV 7S domain. Low doses of a well-known PMI benzoisothiazolone inhibitor impair the growth of diverse strains of B. burgdorferi in culture, but not other tested Gram-negative or Gram-positive pathogens. Borrelia cells are even more susceptible to several other structurally related benzoisothiazolone analogs. The passive transfer of anti-BbPMI antibodies in ticks can impact spirochete transmission to mice, while the treatment of collagen IV-containing murine skin with PMI inhibitors impairs spirochete infectivity. Taken together, these results highlight a newly discovered role for BbPMI in mediating host-pathogen interactions during the spirochete infectivity process. In turn, this discovery offers an opportunity for the development of a novel therapeutic strategy to combat Lyme disease by preventing the BbPMI interaction with its host receptor, collagen IV.IMPORTANCEAll organisms produce an intracellular enzyme, phosphomannose isomerase (PMI), that converts specific sugars during metabolism. Unexpectedly, we discovered an additional PMI function in Borrelia burgdorferi, the Lyme disease pathogen, where the enzyme is localized on the cell surface and binds to collagen IV—a host extracellular molecule mainly found in the skin. Low doses of PMI chemical inhibitors impair the growth of diverse strains of B. burgdorferi in culture, but not other tested bacterial pathogens. The passive transfer of anti-BbPMI antibodies in ticks can impact B. burgdorferi transmission to mice, while the treatment of collagen IV-containing murine skin with PMI inhibitors impairs infectivity. Taken together, these results highlight a newly discovered role for BbPMI in mediating host-pathogen interactions during infection. In turn, this discovery offers an opportunity for the development of a novel therapeutic strategy to combat Lyme disease by preventing BbPMI function and interaction with host collagen IV.